161k views
4 votes
Let p= x^2-7.

which equation is equivalent to (x^2-7)-4x^2+28 in terms of p

PLZ HELP

Let p= x^2-7. which equation is equivalent to (x^2-7)-4x^2+28 in terms of p PLZ HELP-example-1
User JWiley
by
5.4k points

2 Answers

4 votes

Final answer:

To find an equation equivalent to (x^2-7)-4x^2+28 in terms of p, substitute x^2-7 with p. The equation equivalent to (x^2-7)-4x^2+28 in terms of p is -4x^2+p+28.

Step-by-step explanation:

To find an equation equivalent to (x^2-7)-4x^2+28 in terms of p, we can substitute x^2-7 with p. So we have (p)-4x^2+28. Now, we combine like terms by adding the coefficients of p and -4x^2, which gives us -4x^2+p+28.

User Ostap Gonchar
by
6.9k points
0 votes

Since p = x² - 7, you can substitute/plug in p for x² - 7

So:

(x² - 7)² - 4x² + 28 = 5

(p)² - 4x² + 28 = 5 You can factor out -4 from (-4x² + 28)

p² - 4(x² - 7) = 5 Plug in p

p² - 4p = 5 Subtract 5

p² - 4p - 5 = 0 Your answer is C

User Aswath
by
6.0k points